False-positive elevation of 1, 3-beta-D-glucan caused by continuous administration of penicillin G. Issue 10 (October 2018) - Ito, Shoko; Ashizawa, Masahiro; Sasaki, Ryo; Ikeda, Takashi; Toda, Yumiko; Mashima, Kiyomi; Umino, Kento; Minakata, Daisuke; Nakano, Hirofumi; Yamasaki, Ryoko; Kawasaki, Yasufumi; Sugimoto, Miyuki; et al.
Abstract: The 1, 3-beta-D-Glucan (BDG) assay is widely used for the diagnosis of fungal infections, especially in patients with hematologic malignancies. Some antimicrobials have been reported to cause false-positive results for BDG, but there has been no report on the effect of penicillin G (PCG) on BDG levels. We experienced a patient who developed false-positive BDG elevation during the administration of PCG for osteomyelitis due to Streptococcus pneumoniae infection. The serum BDG level increased up to 81.0 pg/ml during the continuous administration of PCG at 24 million units per day. However, chest and paranasal CT scan showed no evidence of fungal infection. The BDG level decreased to 38.0 pg/ml at 14 hours after the discontinuation of PCG. The amount of BDG in one vial of PCG inferred from these serum BDG levels is very similar to the actual BDG concentration in a vial of PCG. Therefore, during the administration of PCG, elevated BDG levels should be interpreted with caution, as they may be false-positive results.